2013
DOI: 10.1111/j.1743-498x.2012.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching skills training for medical students

Abstract: Our study demonstrates both the similarities and variation between undergraduate teaching skills courses across England. However, further research will be necessary to determine whether the long-term impact of such training will result in better educators, and ultimately in improved patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Medical schools are starting to recognize the importance of CYPT and almost half of US and UK medical schools now offer some kind of CYPT program [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Medical schools are starting to recognize the importance of CYPT and almost half of US and UK medical schools now offer some kind of CYPT program [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, peer teaching has been widely adopted within undergraduate medical education . There are many advantages of using peer teaching to support faculty member teaching within undergraduate curricula.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of US medical schools showed that only 44% of respondents had formal student‐as‐teacher (SaT) programmes . Additionally, in 2013, only 40% of UK medical schools had compulsory teaching skills development courses within the curricula …”
Section: Introductionmentioning
confidence: 99%